Reflexiones sobre el concepto de documentación audiovisual y de imagen en movimiento en los Sistemas de Información de las televisiones - Caldera Serrano, Jorge (Revista General de Información y Documentación, 2003)
The article deals with a series of peculiarities which distinguish the concept of working document for television information systems. The term, documentation of the moving image —with the possible inclusion of sound, in contrast with the term audiovisual documentation used at present, is proposed as the accepted term. This option has been determined by a series of factors such as the fact that sound is not present in all television documents and also that documents are saved in accordance with their visual and not their audio values. This idea forms part of the Information Management System framework as a valid formula for implementation into organizations and as a model for documental management and organization, taking the documents acquired or generated as unquestionable business assets integral to and inseparable from the organization.